Catalogo de los Diptera de Nicaragua. 6. Ceratopogonidae (Nematocera) - Maes, J.-M.=700 1 Wirth, W.W.
(En, Es)
Ilus., 168 ref
Keywords: CLASIFICACION; INSECTA; DIPTERA; CERATOPOGONIDAE; HUESPEDES; ENEMIGOS NATURALES; TRANSMISION DE ENFERMEDADES; DISTRIBUCION GEOGRAFICA; NICARAGUA; NEMATOCERA; REVISTA NICARAGUENSE DE ENTOMOLOGIA